A Simple Specification Test for the Predictive Ability of Transformation Models - Wooldridge, Jeffrey M. (The Review of Economics and Statistics, 1994)
A specification test is proposed to test the adequacy of the implicit conditional mean specification in a transformation model. Regardless of the transformation under the null, the statistic is computable from ordinary least squares output via auxiliary ordinary least squares regressions. Further, the test presumes no particular form for the conditional variance of the transformed and untransformed regressands. A simple goodness-of-fit measure that can be used to compare across transformations is a natural byproduct of the analysis. An application to a well-known fisheries data set is included. Copyright 1994 by MIT Press.